Durability of protective antibody titres is not enhanced by a two-dose schedule of an ASO3-adjuvanted pandemic H1N1 influenza vaccine in adult HIV-1-infected patients. (September 2014) - Bickel, Markus; Lais, Corinna; Wieters, Imke; Kroon, Frank P.; Doerr, Hans Wilhelm; Herrmann, Eva; Brodt, Hans Reinhard; Jung, Oliver; Allwinn, Regina; Stephan, Christoph
Abstract The immune response after influenza vaccination is impaired in HIV-infected individuals and can be enhanced by a second dose. The durability of the antibody protection and its clinical benefit is not known. We investigated clinical symptoms and antibody titres against H1N1 influenza A following no dose, 1 dose, or 2 doses of an ASO3-adjuvanted H1N1 vaccine in HIV-infected patients. Seroprotection was found in 7.9%, 52.2%, and 57.3% of patients who received no dose, 1 dose, and 2 doses of the vaccine, respectively (p-value for group comparison < 0.001), after a median of 8.2 ± 1.6 months. Clinical symptoms suggestive of an influenza-like illness were slightly more frequently reported in the unvaccinated group. Vaccinated HIV-infected patients were more likely to be seroprotected at follow-up, but there was no difference comparing those who had received 1 or 2 doses of the vaccine.